Incidence and Mortality of Acute Respiratory Distress Syndrome in Patients With Burns: A Systematic Review and Meta-Analysis - Wang, Baoli; Chenru, Wei; Jiang, Yong; Hu, Lunyang; Fang, He; Zhu, Feng; Yu, Qing; Zhu, Banghui; Wu, Guosheng; Sun, Yu; Xia, Zhaofan (Frontiers in Medicine, 2021)
Objective: We conducted a systematic review and meta-analysis to comprehensively estimate the incidence and mortality of acute respiratory distress syndrome (ARDS) in overall and subgroups of patients with burns. Data sources: Pubmed, Embase, the Cochrane Library, CINAHL databases, and China National Knowledge Infrastructure database were searched until September 1, 2021. Study selection: Articles that report study data on incidence or mortality of ARDS in patients with burns were selected. Data extraction: Two researchers independently screened the literature, extracted data, and assessed the quality. We performed a meta-analysis of the incidence and mortality of ARDS in patients with burns using a random effects model, which made subgroup analysis according to the study type, inclusion (mechanical ventilation, minimal burn surface), definitions of ARDS, geographic location, mean age, burn severity, and inhalation injury. Primary outcomes were the incidence and mortality of burns patients with ARDS, and secondary outcomes were incidence for different subgroups. Data synthesis: Pooled weighted estimate of the incidence and mortality of ARDS in patients with burns was 0.24 [95% confidence interval (CI)0.2–0.28] and 0.31 [95% CI 0.18−0.44]. Incidences of ARDS were obviously higher in patients on mechanical ventilation (incidence = 0.37), diagnosed by Berlin definition (incidence = 0.35), and with over 50% inhalation injury proportion (incidence = 0.41) than in overall patients with burns. Patients with burns who came from western countries and with inhalation injury have a significantly higher incidence of ARDS compared with those who came from Asian/African countries (0.28 vs. 0.25) and without inhalation injury (0.41 vs. 0.24). Conclusion: This systematic review and meta-analysis revealed that the incidence of ARDS in patients with burns is 24% and that mortality is as high as 31%. The incidence rates are related to mechanical ventilation, location, and inhalation injury. The patients with burns from western countries and with inhalation injury have a significantly higher incidence than patients from Asian/African countries and without inhalation injury. Systematic Review Registration: identifier: CRD42021144888.